Molecular, Structural and Immunological Characterization of Der p 18, a Chitinase-Like House Dust Mite Allergen - Resch, Yvonne; Blatt, Katharina; Malkus, Ursula; Fercher, Christian; Swoboda, Ines; Focke-Tejkl, Margit; Chen, Kuan-Wei; Seiberler, Susanne; Mittermann, Irene; Lupinek, Christian; Rodriguez-Dominguez, Azahara; Zieglmayer, Petra; et al. (PLoS One, 2016)
BACKGROUND: The house dust mite (HDM) allergen Der p 18 belongs to the glycoside hydrolase family 18 chitinases. The relevance of Der p 18 for house dust mite allergic patients has only been partly investigated. OBJECTIVE: To perform a detailed characterization of Der p 18 on a molecular, structural and immunological level. METHODS: Der p 18 was expressed in E. coli, purified to homogeneity, tested for chitin-binding activity and its secondary structure was analyzed by circular dichroism. Der p 18-specific IgG antibodies were produced in rabbits to localize the allergen in mites using immunogold electron microscopy and to search for cross-reactive allergens in other allergen sources (i.e. mites, crustacea, mollusca and insects). IgE reactivity of rDer p 18 was tested with sera from clinically well characterized HDM-allergic patients (n = 98) and its allergenic activity was analyzed in basophil activation experiments. RESULTS: Recombinant Der p 18 was expressed and purified as a folded, biologically active protein. It shows weak chitin-binding activity and partial cross-reactivity with Der f 18 from D. farinae but not with proteins from the other tested allergen sources. The allergen was mainly localized in the peritrophic matrix of the HDM gut and to a lower extent in fecal pellets. Der p 18 reacted with IgE from 10% of mite allergic patients from Austria and showed allergenic activity when tested for basophil activation in Der p 18-sensitized patients. CONCLUSION: Der p 18 is a rather genus-specific minor allergen with weak chitin-binding activity but exhibits allergenic activity and therefore should be included in diagnostic test panels for HDM allergy.
Keywords: Rabbits; králíci; Sequence Homology, Amino Acid; Protein Binding; sekvenční seřazení; sbalování proteinů; Male; Recombinant Proteins; Gene Expression; Antibodies; lidé; antisérum; proteiny členovců; Protein Interaction Domains and Motifs; sekvence aminokyselin; Chitin; Humans; Cloning, Molecular; interakční proteinové domény a motivy; Animals; exprese genu; chitin; Protein Conformation, alpha-Helical; Arthropod Proteins; konformace proteinů, beta-řetězec; sekvenční homologie aminokyselin; zvířata; protilátky; vazba proteinů; Pyroglyphidae; bazofily; mužské pohlaví; klonování DNA; respirační alergie; Basophils; Sequence Alignment; rekombinantní proteiny; Protein Folding; antigeny roztočů domácího prachu; Respiratory Hypersensitivity; Immune Sera; Protein Conformation, beta-Strand; ženské pohlaví; Antigens, Dermatophagoides; Female; Amino Acid Sequence; Escherichia coli; konformace proteinů, alfa-helix